2003
DOI: 10.1021/ja034983m
|View full text |Cite
|
Sign up to set email alerts
|

Isotope Effect-Mapping of the Ionization of Glucose Demonstrates Unusual Charge Sharing

Abstract: Isotopic substitution is known to affect kinetic rate constants and equilibrium constants in chemistry. In this study, we have used tritium substitution and high pH to probe the glucose left harpoon over right harpoon glucose(-) + H(+) equilibrium. Passing partially ionized mixtures of [(3)H]- and [(14)C]glucose over anionic exchange resin has permitted the detection of subtle differences in pK(a). We have found that, at pH 11.7 in an anionic exchange system, [(3)H]glucose always elutes ahead of the [(14)C]glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
1
12
1
Order By: Relevance
“…Considering additional uncertainties in the pH values when preparing the solutions, a precision of 0.2, yielding 12.2 ± 0.2, is reasonable. This result is in excellent agreement with the value reported from titration-based methods (p K a1 values in the 12.1 to 12.5 range 36 , 37 , 39 41 ). The novelty of our LJ-PES approach is the simultaneous determination of the actual deprotonation site, which allows us to associate site-selective spectral changes with a particular acid-ionization constant.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Considering additional uncertainties in the pH values when preparing the solutions, a precision of 0.2, yielding 12.2 ± 0.2, is reasonable. This result is in excellent agreement with the value reported from titration-based methods (p K a1 values in the 12.1 to 12.5 range 36 , 37 , 39 41 ). The novelty of our LJ-PES approach is the simultaneous determination of the actual deprotonation site, which allows us to associate site-selective spectral changes with a particular acid-ionization constant.…”
Section: Resultssupporting
confidence: 91%
“…This latter finding is in contradiction with the report by Feng et al, 85 who found p K a1 values for C4 and C6 sites to vary between the anomeric forms by more than 2 and 4 p K a units, respectively. Whereas charge sharing between the two most acidic (C1 and C4) sites has been suggested by Lewis and Schramm 39 and cannot be completely excluded based on the C 1s PES experimental data, the present calculations show that C4-deprotonation contributions to the p K a1 equilibrium would be negligibly small. The second acid dissociation constant (p K a2 ) of glucose, assuming deprotonation at C1 followed by deprotonation at C4, was also calculated, yielding a value of 20.8, which is well-separated from the p K a1 value.…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…Both PE and MGlcDAG may also partly phase separate from their lipid environment under certain conditions (62,63), and PE is potentially enriched around membrane proteins in E. coli (64). Likewise, they can both become ionized and engage in hydrogen bonding (65,66), in contrast to phosphatidylcholine, which does not substitute for PE in supporting LacY function (67,68). Finally, the chemical differences between the zwitterionic PE headgroup, and the uncharged, stiff, ring-shaped glucose of MGlcDAG are substantial, although both would dampen the negative charge density of a bilayer composed of only anionic lipids.…”
Section: Discussionmentioning
confidence: 99%
“…In general, secondary hydrogen-deuterium equilibrium isotope effects (EIEs) on gas phase acidities are much smaller (typically $<1 kJ/mol for the a-position, and $<0.5 kJ/mol for the b-position) than primary EIEs [10], for which the experimental database [11] shows an effect typically on the order of $5 to 10 kJ/mol. However, despite the broad interest in isotope effects across all disciplines of chemistry, it appears relatively few experimental or theoretical studies have investigated EIEs on gas phase acidities [10] (of interest, we also note the following EIE solution phase studies on acidity constants [12][13][14][15][16][17][18][19][20][21]). Consequently, in the current work we examine the gas phase acidities of various main group hydrides, carbon acids, and oxyacids and representative isotopologues using high-level theoretical methods, providing comparison to experimental data where possible, and investigating potential periodic trends and other structure-property relationships.…”
Section: Introductionmentioning
confidence: 99%